2021
DOI: 10.1002/hed.26896
|View full text |Cite
|
Sign up to set email alerts
|

Novel loop neurorrhaphy technique to preserve lower lip sensate in mandibular reconstruction using an innervated vascularized iliac bone flap

Abstract: Background: This study aimed to introduce a novel loop neurorrhaphy technique using an innervated vascularized iliac bone flap (VIBF) with vascularized ilioinguinal nerve (IIN) to reconstruct the inferior alveolar nerve (IAN) and preserve lower lip sensation simultaneously with mandibular reconstruction.Methods: This study prospectively included patients who underwent mandibular reconstruction using VIBF from May 2018 to April 2020. Subjects were allocated into two groups: (1) Group I; innervated VIBF with loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“… Author and year Disease P Donor site Evaluation of the function of the jaw and/or mouth and/or the speech apparatus and/or esophagus Evaluation of the global function related to the donor site 31. Abdelrehem et al [ 42 ] AB, OM, malignant tumor of jaw, KCOT n = 12 age 18–57 Innervated vascularizediliac bone No speech disorders in some patients, accidental bites on the lip, salivation 0–3.17 on a scale No restrictions in everyday activities 32. Devireddy et al [ 26 ] OF, AB, KCOT n = 7 age 13–63 Nonvascular fibula graft No restrictions, deviation in one of the directions or no large changes in the jaw movement, no restrictions on tongue mobility, limited opening or improvement of the mouth opening 3.5–4.2 cm No foot drooping 33.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Author and year Disease P Donor site Evaluation of the function of the jaw and/or mouth and/or the speech apparatus and/or esophagus Evaluation of the global function related to the donor site 31. Abdelrehem et al [ 42 ] AB, OM, malignant tumor of jaw, KCOT n = 12 age 18–57 Innervated vascularizediliac bone No speech disorders in some patients, accidental bites on the lip, salivation 0–3.17 on a scale No restrictions in everyday activities 32. Devireddy et al [ 26 ] OF, AB, KCOT n = 7 age 13–63 Nonvascular fibula graft No restrictions, deviation in one of the directions or no large changes in the jaw movement, no restrictions on tongue mobility, limited opening or improvement of the mouth opening 3.5–4.2 cm No foot drooping 33.…”
Section: Resultsmentioning
confidence: 99%
“…They concerned both the craniofacial area and donor sites. These included sensory disturbances in the lips and graft area, or pain in the oral cavity [ 15 17 , 20 , 34 , 42 ]. Some patients also experienced neuropathic pain or local pain in the limb, as well as sense weakness in the donor site area or complete loss of sense along the peroneal nerve [ 14 , 20 , 40 , 41 , 43 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Traditional approaches for repairing maxillofacial bone defects using nonvascularized free bone grafts often result in significant bone resorption and surgical failures, even when the grafts are adequately vascularized. However, our research team has observed that restoration of neural innervation in the transplanted bone can effectively maintain bone mass and preserve the original strength of the graft [ 12 , 16 ]. While autologous bone grafting remains the current gold standard, emerging neovascularized tissue-engineered bone technology offers promising prospects.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective and prospective clinical studies have shown that simultaneous innervated bone grafting can significantly reduce osteoporosis and effectively maintain lower lip sensation. It also suggests that nerves are important in bone homeostasis [ 182 , 183 ]. In recent years, studies in the field of tissue engineering have found that in addition to vascularization, neurogenesis may also be important in promoting the formation of bone [ 167 , 184 , 185 ].…”
Section: Construction Of Innervated Tissue Engineered Bonementioning
confidence: 99%